ANALISIS PENGENDALIAN INTERNAL ATAS PENGELOLAAN BARANG MILIK DAERAH PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUBU RAYA - B51112027, APRIANI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This study aims to determine how is the regional property management in Population and Civil Registration Office of Kubu Raya, how is the effectiveness of internal control over regional property management in Population and Civil Registration Office of Kubu Raya is, and What are the factors that influence the effectiveness of control over the regional property management in Population and Civil Registration Office of Kubu Raya. The method used is descriptive method with qualitative approach. The analysis tool used is the Indonesian Government Regulation No. 27 of 2014 on Management of State/Regional Property, Kubu Raya Regional Regulation No. 3 of 2015 on Regional Property Management and Internal Control Questionnaire. The results of this study indicate that the internal control over regional property management in the Population and Civil Registration Office of Kubu Raya is effective. And overall the regional property management has been done in accordance with Governmental Regulation No.27 of 2014 and Regional Regulation No.3 of 2015, but the Population and Civil Registration Office of Kubu Raya did not do utilization, physical safeguards for land and building, alienation and destruction, and there are still weaknesses in the employee in terms of demand planning and budgeting, utilization, security, destruction, surveillance and control, and there are employees who have double work so that the effectiveness of employees in performing their duties should be corrected and addressed. Keyword: Regional Property, PP No.27/2014, Perda No.3/2015, Effectiveness